2015
DOI: 10.1021/acs.chemmater.5b03877
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Evidence for Low Charging Overpotentials of Superoxide Discharge Products in Metal–Oxygen Batteries

Abstract: Li–oxygen and Na–oxygen batteries are some of the most promising next-generation battery systems because of their high energy densities. Despite the chemical similarity of Li and Na, the two systems exhibit distinct characteristics, especially the typically higher charging overpotential observed in Li–oxygen batteries. In previous theoretical and experimental studies, this higher charging overpotential was attributed to factors such as the sluggish oxygen evolution or poor transport property of the discharge p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 53 publications
13
73
0
3
Order By: Relevance
“…However, computations suggest that the energy barrier of the disproportionation of large LiO 2 clusters is significantly higher than that of the LiO 2 dimer, indicating that the disproportionation rate of large clusters is much slower than that of the dimer. [75] Besides, the solution mediated mechanism of charging was also investigated and the dissolution energy of LiO 2 is lower than that of Li 2 O 2 . Then, in 2016, Lu et al [74] provided evidence that it is possible to have a one-electron discharge process with forming only LiO 2 in a LiÀO 2 battery.…”
Section: Charge Transfermentioning
confidence: 99%
“…However, computations suggest that the energy barrier of the disproportionation of large LiO 2 clusters is significantly higher than that of the LiO 2 dimer, indicating that the disproportionation rate of large clusters is much slower than that of the dimer. [75] Besides, the solution mediated mechanism of charging was also investigated and the dissolution energy of LiO 2 is lower than that of Li 2 O 2 . Then, in 2016, Lu et al [74] provided evidence that it is possible to have a one-electron discharge process with forming only LiO 2 in a LiÀO 2 battery.…”
Section: Charge Transfermentioning
confidence: 99%
“…[1] In addition, similar studies of the Na-O2 system also suggest that conductivity of NaO2 is limited and that discharge by a surface route is not a dominant discharge pathway, [14,22] although calculation shows that NaO2 has a higher conductivity than LiO2. [23] Since the K-O2 battery was reported in 2013, [8] only a few studies of the system have been reported and the discharge mechanism in the K-O2 battery remains poorly understood. [24][25][26][27] Here we explore discharge in the K-O2 battery using solvents that are expected to induce a surface route.…”
Section: Cathodementioning
confidence: 99%
“…Hence, very few reports focused on developing catalysts for Na-O 2 and K-O 2 superoxide batteries. [16] They found that the OER barriers at major surfaces of the superoxides were substantially lower than those of the peroxides. [15] Theoretical calculations were conducted to address the discrepancy in the charge overpotential between peroxides and superoxides.…”
Section: Solid State Catalyst To Lower Charge Potentialmentioning
confidence: 99%